Taxonomic revision of Dichotomius (Selenocopris) nisus (Olivier, 1719) and Dichotomius (Selenocopris) superbus (Felsche, 1901) - Cassenote,Sheila (2020)
Abstract Within the subgenus Dichotomius (Selenocopris) Burmeister 1846, D. nisus (Olivier, 1789) and D. superbus (Felsche, 1901) had been historically arranged in the “Nisus” section by Luederwaldt, however, according to the revised classification of the subgenus, the two species now belong to different species groups. In this paper, the taxonomic history concerning the species once included by Luederwaldt in the “Nisus” section is revised and discussed. The following new synonyms are proposed: Pinotus taunayi (Luederwaldt, 1931) as a subjective synonym of D. geminatus (Arrow, 1913), and Pinotus taunayi pilosus (Luederwaldt, 1931) as a subjective synonym of D. nisus. Lectotypes are designated for D. nisus and Pinotus garbei. Redescriptions, diagnoses and updated distribution data are provided for D. nisus and D. superbus. The diagnostic characters of the male genitalia of these species are described and illustrated for the first time.